Navigating The Cross-Cultural Challenges of the Philippine Contingent in the United Nations Mission in South Sudan (UNMISS): An Ethnographic Study - Manlapaz – Fabro, Jhoanna Gracia; Fabro, Arvin B.; Tanigue, Yolanda G.; Pareja, Teresita P. (Future Science / FSH-PH Publications, 2025)
This ethnographic study investigates into the cross-cultural challenges faced by 23 Filipino Individual Police Officers (IPOs) serving in the United Nations Mission in South Sudan (UNMISS). This research employs qualitative methods, including structured interviews and participant observation, to explore the impact of cultural differences on performance, communication, and interpersonal relationships within a diverse peacekeeping environment. This research explores three pivotal inquiries: What shared cultural insights do Filipino IPOs recognize in UNMISS? What particular obstacles are they encountering? What effects do these challenges have on their performance? The findings reveal that cultural differences—especially in language, communication styles, and work ethics—resulted in misunderstandings and operational challenges, yet they also fostered growth. Filipino IPOs showcased remarkable adaptability, patience, and resilience, enhancing collaboration and elevating cultural sensitivity. The research suggests implementing focused strategies, including pre-deployment training, psychological evaluations centered on cultural adaptability, and mentorship initiatives. This research offers valuable insights into the intricacies of intercultural dynamics within peacekeeping missions. It highlights the critical need to support peacekeepers, thereby boosting their effectiveness and showcasing Filipino cultural values on the international stage.